A transputer-based PID/Neural network controller for DC servo motor control - Kommalur Giridhara. (2009)
The rapid and revolutionary progress in power electronics and microelectronics in recent years has made it possible to apply modern control technology which has gone through evolution during the last three decades to the area of servo motor and motion control. Currently, microprocessor-based controllers are invariably used in most applications of drive electronics. Although the transputers have been developed primarily for applications in the field of parallel processing, recently they have been used in digital servo motor and motion control because of their suitable architecture and fast computation capability. The use of transputers has permitted the increasingly stringent performance requirements, fast, efficient, and accurate control of servo motor and motion control systems.